Governing 'levelling-up' in the UK: challenges and prospects. Issue 5 (8th December 2021) - Connolly, John; Pyper, Robert; van der Zwet, Arno
ABSTRACT: Following the Conservative Party's victory in the 2019 UK General Election, and its success in achieving significant electoral gains across traditional Labour Party 'red' areas in the north of England, Prime Minister Boris Johnson vowed not to let down the new Conservative voters and pledged that his government would address longstanding regional inequalities in the UK. Consequently, 'levelling up' became part of the public policy lexicon, and, in March 2021, the government published its Levelling Up Fund prospectus. The concept of levelling up enjoys widespread political support, has featured in important policy initiatives beyond the UK, and has been the subject of considerable theorising. This article considers how social scientists might evaluate the success or otherwise of the UK government's levelling-up agenda. The article suggests that any evaluation of this agenda requires the need to take into account aspects of network complexity, the resource allocation arrangements attached to the policy, and what the policy signifies in terms of governance leadership in the context of delivering public value. The article concludes that the UK government's plans risk falling short of delivering a sustained reform programme to reduce area-based inequalities.